Eicosapentaenoic and Docosahexaenoic Acids Attenuate Progression of Albuminuria in Patients With Type 2 Diabetes Mellitus and Coronary Artery Disease. Issue 7 (14th July 2017) - Elajami, Tarec K.; Alfaddagh, Abdulhamied; Lakshminarayan, Dharshan; Soliman, Michael; Chandnani, Madhuri; Welty, Francine K.
Abstract : Background: Albuminuria is a marker of inflammation and an independent predictor of cardiovascular morbidity and mortality. The current study evaluated whether eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) supplementation attenuates progression of albuminuria in subjects with coronary artery disease. Methods and Results: Two‐hundred sixty‐two subjects with stable coronary artery disease were randomized to either Lovaza (1.86 g of EPA and 1.5 g of DHA daily) or no Lovaza (control) for 1 year. Percent change in urine albumin‐to‐creatinine ratio (ACR) was compared. Mean (SD) age was 63.3 (7.6) years; 17% were women and 30% had type 2 diabetes mellitus. In nondiabetic subjects, no change in urine ACR occurred in either the Lovaza or control groups. In contrast, ACR increased 72.3% ( P <0.001) in diabetic subjects not receiving Lovaza, whereas those receiving Lovaza had no change. In diabetic subjects on an angiotensin‐converting enzyme‐inhibitor or angiotensin‐receptor blocker, those receiving Lovaza had no change in urine ACR, whereas those not receiving Lovaza had a 64.2% increase ( P <0.001). Change in ACR was directly correlated with change in systolic blood pressure ( r =0.394, P =0.01). Conclusions: EPA and DHA supplementation attenuated progression of albuminuria in subjects with type 2 diabetes mellitus and coronary artery disease, most of whom were on an angiotensin‐converting enzyme‐inhibitor or angiotensin‐receptor blocker. Thus, EPA and DHA supplementation should be considered as additional therapy to an angiotensin‐converting enzyme‐inhibitor or angiotensin‐receptor blocker in subjects with type 2 diabetes mellitus and coronary artery disease. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01624727.